Glyco-engineering for biopharmaceutical production in moss bioreactors - Decker, Eva L.; Parsons, Juliana; Reski, Ralf (Frontiers in Plant Science, 2014)
The production of recombinant biopharmaceuticals (pharmaceutical proteins) is a strongly growing area in the pharmaceutical industry. While most products to date are produced in mammalian cell cultures, namely CHO cells, plant-based production systems gained increasing acceptance over the last years. Different plant systems have been established which are suitable for standardization and precise control of cultivation conditions, thus meeting the criteria for pharmaceutical production. The majority of biopharmaceuticals comprise glycoproteins. Therefore, differences in protein glycosylation between humans and plants have to be taken into account and plant-specific glycosylation has to be eliminated to avoid adverse effects on quality, safety and efficacy of the products. The basal land plant Physcomitrella patens (moss) has been employed for the recombinant production of high-value therapeutic target proteins (e.g., Vascular Endothelial Growth Factor, Complement Factor H, monoclonal antibodies, Erythropoietin). Being genetically excellently characterized and exceptionally amenable for precise gene targeting via homologous recombination, essential steps for the optimization of moss as a bioreactor for the production of recombinant proteins have been undertaken. Here, we discuss the glyco-engineering approaches to avoid non-human N- and O-glycosylation on target proteins produced in moss bioreactors.